Design, simulation and performance evaluation of vertical axis helical wind turbine - Karki, Bikash; Subedi, Ashok; Sigdel, Himal; Bartaula, Pradeep (Journal of Innovations in Engineering Education, 2019)
This report is all about the design, simulation, fabrication, and performance evaluation of the VAHWT. The experimental data obtained via testing and data from CFD approach are used for performance evaluation. From the data obtained experimentally, the VAHWT so fabricated has been found to operate at the low cut-in speed of 3.18 m/s and maximum power output has been found to be 2.656 watts at the wind speed of 8 m/s. The maximum rpm of the rotor blade is recorded to be 722.2 rpm at the velocity of 11.53 m/s signifying its potentiality of wind power production. Besides, the data so obtained from both the process when analyzed through graph plots, has shown the similar nature slope wise. This simply signifies the generation of satisfactory data via experiment. In addition, the mechanical losses has shown difference between the experimental and data obtained via CFD approach. At the end, when applying CFD approach for evaluation of maximum efficient turbine varying the aspect ratio, has shown the turbine with aspect ratio of 0.6531 to be the most efficient with performance coefficient of 36.396%. However due to limitation in RPM and Test rig, the rotor blade with aspect ratio of 0.6956 was fabricated and used for evaluation experimentally. The data so obtained from both the process were concluded to be relevant to each other. Thus, the detail study on this project has led to the need and opportunity of VAHWT to be further researched and can be developed as a good source of energy producing system. It can also be economical method of power extraction from wind in the countries like Nepal with growing urbanization.